Relationship between Social Media Collaboration and Ecosystem Management in Enugu State, Nigeria - Agbaeze, Emmanuel K; Onyinye, Ajoku P.P.; Joseph, Obamen; Solomon, Omonona (Journal of Economics and Behavioral Studies, 2018)
This study was done on the relationship between social media collaborations and ecosystem management in Enugu state. The study was premised on the case of herdsmen-farmers/villagers clash over grazing fields and farmlands in Enugu State being the ecology-related issue. Survey research design was adopted for the study. A sample of 100 social media group participants was selected using snowball sampling technique. The questionnaire was used for data collection. Content validity was used as a method for testing the validity of the questionnaire while Cronbach’s alpha method was used for testing the internal consistency of the items on the questionnaire. Pearsonâ€™s Product Moment Correlation was used to test the hypothesis formulated for the study. Findings revealed that social media collaborations via Facebook, WhatsApp and Twitter have a significant relationship with ecosystem management. It was recommended that government and ecologically concerned agencies should employ social media collaborations as the policy for ecosystem management.